Oxygen Vacancies in Oxide Nanoclusters: When Silica Is More Reducible Than Titania - Cuko, Andi; Bromley, Stefan T.; Calatayud, Monica (Frontiers in Chemistry, 2019)
Oxygen vacancies are related to specific optical, conductivity and magnetic properties in macroscopic SiO2 and TiO2 compounds. As such, the ease with which oxygen vacancies form often determines the application potential of these materials in many technological fields. However, little is known about the role of oxygen vacancies in nanosized materials. In this work we compute the energies to create oxygen vacancies in highly stable nanoclusters of TiO2, SiO2 and mixed TixSi1-xO2 for sizes between 2 and 24 units. Contrary to the results for bulk and surfaces, we predict that removing an oxygen atom from silica is energetically more favourable than from titania. This unexpected chemical behaviour is clearly linked to the small size of the systems considered. In order to fully characterise our findings, we provide an extensive set of descriptors (oxygen vacancy formation energy, electron localization, density of states, relaxation energy and geometry) that can be used to compare our results with those for other compositions and sizes. Our results will help in the search of novel nanomaterials for technological and scientific applications such as heterogeneous catalysis, electronics and cluster chemistry.